The effect of levodopa in combination with Hank's balanced salt solution in enhancing periodontal ligament cell viability: An in vitro study - Smita P Patil; Prashant B Patil; Meena V Kashetty (Wolters Kluwer Medknow Publications, 2020)
Aim: This study aims to study the viable property of periodontal ligament (PDL) cells in the avulsed teeth using Hank's balanced salt solution (HBSS) storage medium with levodopa (L-dopa) and without L-dopa. Materials and Methods: The study samples included 40 freshly extracted, noncarious, non-impacted human teeth with closed apices. The teeth were then randomly divided into four groups containing four different experimental storage solutions, namely Group 1: Deionized water; Group 2: Deionized water with L-dopa (1 μg/μl); Group 3: HBSS; and Group 4: HBSS with L-dopa (1 μg/μl). All the teeth were stored in different test solutions for 60 min. Collagenase assay was performed followed by analyses of the number of viable PDL cells using a hemocytometer under a light microscope at ×20 magnification. The mean and standard deviation (SD) of viable PDL cells of all the four groups obtained were evaluated using Kruskal-Wallis test. P < 0.001 was considered statistically significant. Comparison between the four groups was done using Mann-Whitney test and U <23 and P < 0.05 was considered statistically significant. Results: Comparison of mean and SD of viable PDL cells showed a significant difference between the four groups (P < 0.001). Group 4 showed the highest mean number of PDL cells, followed by Group 3, Group 2, and Group 1, respectively. These findings indicate that the viability of PDL cells was highest when teeth were stored in HBSS with L-dopa, followed by HBSS, than de-ionized water with L-dopa and least in de-ionized water. Conclusion: The results of the study showed that the PDL cells were rendered more viable by the synergistic effect of L-dopa along with HBSS as a storage medium for an avulsed tooth.